2001
DOI: 10.1116/1.1410091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of new x-ray stepper, the XRA

Abstract: The exposure performance has been evaluated for the new x-ray stepper, the XRA, which is equipped with global alignment and magnification correction systems. Dose uniformity in the exposure field of 3.9%, stage accuracy of less than 20 nm, and good linearity and stability between the magnification change and applied force were obtained. For the 100 nm node, both critical dimension (CD) control of 10 nm and overlay accuracy of less than 30 nm were obtained using two 4 Gbit masks of the gate and contact hole by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…4,5) As for the printing accuracy, the CD controllability of better than 10 nm (3) and the alignment accuracy within 20 nm (3) are achieved at the gap of 10 m, and the overlay accuracies of less than 30 nm (3) are achieved between gate and contact layers, which satisfy the specifications required at the 100 nm node. 6) It was also found that the PXL has a high fidelity for line and space (L&S), hole and twodimensional patterns of 70 nm at the gap of 10 m. 7) Thus, the specifications required at the 100 nm node have already been achieved in PXL, except for mask defects. Now, we are interested in realizing the resolution extendibility toward 50 nm and below.…”
Section: Introductionmentioning
confidence: 97%
“…4,5) As for the printing accuracy, the CD controllability of better than 10 nm (3) and the alignment accuracy within 20 nm (3) are achieved at the gap of 10 m, and the overlay accuracies of less than 30 nm (3) are achieved between gate and contact layers, which satisfy the specifications required at the 100 nm node. 6) It was also found that the PXL has a high fidelity for line and space (L&S), hole and twodimensional patterns of 70 nm at the gap of 10 m. 7) Thus, the specifications required at the 100 nm node have already been achieved in PXL, except for mask defects. Now, we are interested in realizing the resolution extendibility toward 50 nm and below.…”
Section: Introductionmentioning
confidence: 97%
“…A smaller gap improves the resolution, and exposure at a gap of 10 m has been achieved. 1 The resolution derived by the Fresnel-Kirchhoff diffraction is also improved by using a shorter wavelength x ray, but it has been generally considered that the secondary electron blur increases in a shorter x-ray wavelength region, and the resolution degrades. We have reported that the secondary electron blur can be suppressed in a specified wavelength region shorter than the absorption edge of additive atoms such as Cl, Br, or Si in a resist.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane-based photomasks are used in proximity X-ray lithography [1][2][3][4] including that in LIGA (Lithographie, Galvanoformung und Abformung) process, [5][6][7][8][9] and near-field photolithography, 10,11) where accurate mask configuration and pattern placement are required from mass-production standpoints. Figure 1 shows a schematic view of the proximity X-ray lithography as an example of the lithography using the membrane-based photomask, where the X-ray mask consist of absorber fine pattern, membrane window, Si wafer and support plate, and X-ray mask and processing Si wafer with resist are set with proximity maskwafer gap around 5-20 m in the exposure process.…”
Section: Introductionmentioning
confidence: 99%